Comparative effectiveness of dienogest versus ethinyl estradiol/levonorgestrel combined oral contraceptive therapy in women with endometriosis-associated chronic pelvic pain - Bushra Bahar; Neena Gupta; Alok Raghav; Uruj Jahan; Rashmi Yadav (Frontiers in Endocrinology, 2026)
Objective To compare the clinical effectiveness of combined oral contraceptive pills (levonorgestrel-containing COC) and dienogest in the management of endometriosis-associated chronic pelvic pain and related symptoms. Methods This prospective observational cohort study was conducted in the Department of Obstetrics and Gynecology at GSVM Medical College, Kanpur, India, between 2023 and 2024. A total of 140 women with clinically and ultrasonographically diagnosed endometriosis-associated pelvic pain completed the study and were included in the final analysis. Participants received either dienogest (2 mg once daily) or a continuous combined oral contraceptive containing ethinyl estradiol 0.03 mg and levonorgestrel 0.15 mg for 3 months. Pain severity was assessed using the Visual Analog Scale (VAS) at baseline and during monthly follow-up visits. Longitudinal changes in pain scores and associated symptoms were compared between the treatment groups. Results Baseline demographic and clinical characteristics were comparable between the groups. The mean age of participants in the OCP and dienogest groups was 31.47 ± 8.90 and 31.08 ± 8.78 years, respectively (p=0.794). Baseline mean VAS scores were 8.55 ± 0.98 and 7.77 ± 0.90 in the OCP and dienogest groups, respectively. A significant reduction in VAS scores was observed in both groups throughout the follow-up period (p<0.001). At 3 months, the mean VAS score decreased to 4.28 ± 1.15 and 5.22 ± 1.66 in the OCP and dienogest groups, respectively (p<0.001). Significant improvement in dysmenorrhea, dyspareunia, menstrual irregularities, and chronic pelvic pain was also observed in both groups during follow-up. Conclusion Both treatments were associated with significant improvement in endometriosis-associated pain, and the OCP group showed greater short-term pain reduction in this cohort, suggesting that the evaluated levonorgestrel/ethinyl estradiol regimen may represent a conservative treatment option, particularly in resource-limited healthcare settings. Larger multicenter longitudinal studies are warranted to further validate these findings.